2017
DOI: 10.5897/jhf2015.0406
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of potato production, marketing, and utilization in North Western Amhara Region, Ethiopia

Abstract: on 158 farmers in 2010 to 2011. The main objective of the study was to characterize and document as well as to assess the challenges of existing potato production, marketing and utilization systems based on primary and secondary data. Potato is mainly produced in main, residual and irrigation production seasons in the study zones. Farmers plow their potato farm at least four times before planting and cultivate two to four times. They use an average potato seed tuber rate of about 2.008 tons per hectare. Farmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
6
12
1
Order By: Relevance
“…'Abalo' is predominantly grown in sub-moist (dry) agro-ecology because it is drought tolerant while 'Siquare' is a dominant variety in moist agro-ecology. Yazie et al (2009) and Labarta et al (2012) also reported that 'Siquare' and 'Abalo' are the major potato varieties in the Amhara region but neither study mentioned 'Samune', which is mainly grown in sub-humid and acid soil areas in the region. 'Siquare' is also widely grown in other moist and cool Amhara region districts, including Sinan and Bibugn (Yazie et al 2009) and in some parts of the SNNP and Oromia regions (Labarta et al 2012).…”
Section: Discussion Variety Diversity At Household Level and Distribumentioning
confidence: 94%
See 2 more Smart Citations
“…'Abalo' is predominantly grown in sub-moist (dry) agro-ecology because it is drought tolerant while 'Siquare' is a dominant variety in moist agro-ecology. Yazie et al (2009) and Labarta et al (2012) also reported that 'Siquare' and 'Abalo' are the major potato varieties in the Amhara region but neither study mentioned 'Samune', which is mainly grown in sub-humid and acid soil areas in the region. 'Siquare' is also widely grown in other moist and cool Amhara region districts, including Sinan and Bibugn (Yazie et al 2009) and in some parts of the SNNP and Oromia regions (Labarta et al 2012).…”
Section: Discussion Variety Diversity At Household Level and Distribumentioning
confidence: 94%
“…At Banja, where the soil is highly acidic, farmers don't use chemical fertilizers at all; instead most of the farmers use compost and animal manure as revealed from focus group discussions. Previously, Yazie et al (2009) had reported that 82.5 % of the farmers in the Awi zone, which includes the Banja district, apply manure and compost for their potato crop. Most of the farmers in Shashemene (72 %) and Quarit (68 %) and some farmers in Yilmana (25 %) apply only di-ammonium phosphate (DAP); this is not what the Adet and Holetta Agricultural Research Centers recommend, which is application of both di-ammonium phosphate and urea (Desta et al 2008;Woldegiorgis et al 2008).…”
Section: Potato Production Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The country has four distinct seasons (Belg, Meher, Belmehr and Mesino) for production and these have been described by a number of workers (Gebremedhin et al 2008;Agajie et al 2008;Yazie et al 2009;Gildemacher et al 2009a;Kolech et al 2015). There is some confusion in the literature about seasons of potato production due to a lack of distinction between the Belmehr and Meher seasons (Kolech et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is a cropping season for residual potato and barley production immediately following the main rainy season. Some farmers in the moist agroecological zone of northwest Ethiopia grow potato in this season, however, yield is very low (Yazie et al 2009;Kolech et al 2015).…”
Section: Introductionmentioning
confidence: 99%